Wild Bumblebee (Bombus) Diversity and Nosema (Microsporidia: Nosematidae) Infection Levels Associated with Lowbush Blueberry (Vaccinium angustifolium) Production and Commercial Bumblebee Pollinators. (3rd October 2012) - Bushmann, Sara L.; Drummond, Francis A.; Beers, Lee A.; Groden, Eleanor
Abstract : The primary objective was to determine if the prevalence of Nosema bombi infection is higher for wild bumblebees ( Bombus spp.) caught in lowbush blueberry growing areas with a history of commercial bumblebee use than for bumblebees caught in areas without a history of commercial bumblebee use. Additionally, we wished to determine relative Bombus species abundances and diversity in blueberry growing regions. Over two years we caught, identified to species, and dissected 767 bumblebees. Light microscopy revealed overall infection levels of 5.48%. The history of commercial bumblebee use had no relation to infection levels. Bumblebee species diversity and field location had significant relationships to infection (r 2 adjusted = 0.265; species diversityF ( 1, 22 ) = 6.848, P = 0.016 ; field regionF ( 1, 22 ) = 5.245, P = 0.032 ). The absence or presence of one species, Bombus terricola, appears to determine the relationship between species diversity and infection. The data show B. terricola decline in sampled regions and almost half of the collected B. terricola were infected with Nosema . The commercial species, B. impatiens, shows an increase in abundance, but with a 6.9% proportion infection. Molecular confirmation of the infecting species was ambiguous, suggesting a need for future clarification of the infecting species.